Республика Корея - Толорая Георгий Давидович (Наши деловые партнеры, 1991)
Экземпляры: КХ (20101022) / Инвентарный номер: 987269 / Цена: / Сис.шифр: 65.9(4/8) / Авт.знак: Р 43 / ГРНТИ: 06.91 / ББК: 65.9(5Кор)